Pertubuhan Peladang Kawasan Parit Sulong / Siti Norliyana Kamarudin - Kamarudin, Siti Norliyana (Faculty of Business and Management, 2023)
My industrial training program at Pertubuhan Peladang Kawasan Parit Sulong is discussed in this report. My six-month industrial training program, which ran from 1st March 2023 to 15th August 2023, is now complete. In my internship report, I have included every significant feature of the business that I saw throughout my industrial training program, including PPK Parit Sulong's products and services, its organizational structure, and more. I did not work primarily in any one area throughout my internship program, but I did assist every department that required assistance. In addition to a detailed job description, I have supplied information regarding my six months of employment at Pertubuhan Peladang Kawasan Parit Sulong as well as the knowledge and skills I picked up throughout my industrial training. For instance, I received training on how to handle administrative tasks like writing letters, taking minutes at meetings for administration meetings, answering incoming calls, and performing special tasks like creating posters and memos for PPK Parit Sulong's news, information, and events. I also gained exposure to the organization's various activities. I benefited and learned a lot from the tasks assigned, including how to be more timely, communicate better, and work as a team. Also, I did a SWOT analysis of Pertubuhan Peladang Kawasan Parit Sulong for this report. PPK Parit Sulong's SWOT analysis identifies its advantages and disadvantages from both an internal and external perspective. After a few months, I learned that the SWOT evaluation of my industrial training was complete. It was challenging at first to list this organization's SWOT. I can learn it, though, with the assistance of the staff. It describes the strength, opportunities, threats, and weaknesses of PPK Parit Sulong that affected the organization's business. My recommendations and analysis, which are based on a SWOT analysis, are summarized at the end of the report to help PPK Parit Sulong become a better and more successful business in the future. Last but not least, all of the experiences I had at PPK Parit Sulong had a positive effect on me and will be useful in my future career.